PEMBERDAYAAN PEREMPUAN MELALUI INOVASI PANGAN LOKAL UNTUK MENCEGAH STUNTING - Wahyuni, Ruslina Dwi; Syawalsih, Tourizma Rizky; Rangkuti, Fatmah; Rashed, Azhar (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
This community service aims to prevent stunting by increasing community creativity in processing food ingredients based on local wisdom. One of the main causes of stunting is the inadequacy of nutritional needs in children. Innovation is needed to overcome the problem of stunting, including empowering women and utilizing local food ingredients. Women play an important role in preventing stunting by increasing their creativity in utilizing local food. By encouraging women to use local ingredients in innovating new recipes and cooking techniques, in addition to increasing the nutritional value of food, we also preserve community traditions. This effort not only overcomes existing obstacles but also encourages the realization of gender equality by empowering women to become agents of change. Community service was carried out in Gambirmanis Village, Pracimantoro District, Wonogiri Regency. The method of implementing this community service uses Participatory Action Research (PAR) in the form of workshops, discussions, and direct practice. The PAR work step cycle is to know, to understand, to plan, to act, and to change. The results of this activity were that the participants were enthusiastic in participating in the nutritious food innovation training program, thereby increasing community creativity in innovating to process nutritious food by utilizing local wisdom.